Stem cells as potential therapeutics for hearing loss - Fang, Qiaojun; Wei, Yongjie; Zhang, Yuhua; Cao, Wei; Yan, Lin; Kong, Mengdie; Zhu, Yongjun; Xu, Yan; Guo, Lingna; Zhang, Lei; Wang, Weiqing; Yu, Yafeng; et al. (Frontiers in Neuroscience, 2023)
Hearing impairment is a global health problem. Stem cell therapy has become a cutting-edge approach to tissue regeneration. In this review, the recent advances in stem cell therapy for hearing loss have been discussed. Nanomaterials can modulate the stem cell microenvironment to augment the therapeutic effects further. The potential of combining nanomaterials with stem cells for repairing and regenerating damaged inner ear hair cells (HCs) and spiral ganglion neurons (SGNs) has also been discussed. Stem cell-derived exosomes can contribute to the repair and regeneration of damaged tissue, and the research progress on exosome-based hearing loss treatment has been summarized as well. Despite stem cell therapy's technical and practical limitations, the findings reported so far are promising and warrant further investigation for eventual clinical translation.